2014
DOI: 10.1016/j.orcp.2014.10.146
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of food addiction as assessed by the Yale Food Addiction Scale: A systematic review

Abstract: Obesity is a global issue and it has been suggested that an addiction to certain foods could be a factor contributing to overeating and subsequent obesity. Only one tool, the Yale Food Addiction Scale (YFAS) has been developed to specifically assess food addiction. This review aimed to determine the prevalence of food addiction diagnosis and symptom scores, as assessed by the YFAS. Published studies to July 2014 were included if they reported the YFAS diagnosis or symptom score and were published in the Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
48
2
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 16 publications
9
48
2
2
Order By: Relevance
“…The brain circuits responsible for cravings associated with obesity due to overeating or with drug addiction share extensive overlap. 20,21,73 Perhaps the most convincing account of such overlap was demonstrated by Mantione et al, who reported that stimulation of the nucleus accumbens (NAc) in a patient with OCD led to weight loss and enabled him to quit his long-standing nicotine habit.…”
Section: Future Dbs Targets For Obesitymentioning
confidence: 99%
“…The brain circuits responsible for cravings associated with obesity due to overeating or with drug addiction share extensive overlap. 20,21,73 Perhaps the most convincing account of such overlap was demonstrated by Mantione et al, who reported that stimulation of the nucleus accumbens (NAc) in a patient with OCD led to weight loss and enabled him to quit his long-standing nicotine habit.…”
Section: Future Dbs Targets For Obesitymentioning
confidence: 99%
“…Hence, we can use these generic risk factors -including prior deliberate self-harm, substance use and severe mental illness -to identify adults at risk for premature mortality, of which several are amenable to intervention, even starting in childhood. 18 It is no coincidence that the increasing prevalence of addiction to hyperpalatable obesogenic foods 20 and the emergence of "globesity" 21 have led many to view obesity as a noncommunicable disease, and one whose major impact on premature mortality has yet to be realized. 22 Those predisposed to food addiction also tend to have higher depression scores, 20 a greater likelihood of having been abused as a child 23 and less access to physical activity facilities, especially in areas with low socioeconomic status and among certain minority groups, 24 including Indigenous children and youth.…”
mentioning
confidence: 99%
“…18 It is no coincidence that the increasing prevalence of addiction to hyperpalatable obesogenic foods 20 and the emergence of "globesity" 21 have led many to view obesity as a noncommunicable disease, and one whose major impact on premature mortality has yet to be realized. 22 Those predisposed to food addiction also tend to have higher depression scores, 20 a greater likelihood of having been abused as a child 23 and less access to physical activity facilities, especially in areas with low socioeconomic status and among certain minority groups, 24 including Indigenous children and youth. 25 Certainly, acknowledgement of and proper accounting for these and other inequities can help young adult populations to achieve a healthier body mass, as highlighted in the current issue of Health Promotion and Chronic Disease Prevention in Canada, by Bhawra et al, 25 Frankish et al 26 and Rao et al 27 In another paper published in the current issue, Steensma and colleagues present national data on health-adjusted life expectancy (HALE)-a hybrid measure not only of quantity of life, but of quality of life as well.…”
mentioning
confidence: 99%
“…Il Ce n'est pas un hasard si l'augmentation de la prévalence de la dépendance à l'égard des aliments obésogènes hyper-savoureux 20 et si l'émergence de l'obésité à l'échelle mondiale 21 ont amené de nombreuses personnes à considérer l'obésité comme une maladie non transmissible, dont l'impact majeur sur la mortalité prématurée n'a pas encore été établi 22 . Les personnes prédispo-sées à la dépendance alimentaire ont égale-ment tendance à afficher des scores plus élevés aux questionnaires mesurant la dépression 20 et sont également plus nombreuses à avoir été victimes de violence durant leur enfance 23 et à avoir eu un accès plus limité à des installations facilitant l'activité physique, en particulier dans des régions où le statut socioéconomique est faible et au sein de certains groupes minoritaires 24 , dont les enfants et les adolescents autochtones 25 .…”
unclassified
“…Les personnes prédispo-sées à la dépendance alimentaire ont égale-ment tendance à afficher des scores plus élevés aux questionnaires mesurant la dépression 20 et sont également plus nombreuses à avoir été victimes de violence durant leur enfance 23 et à avoir eu un accès plus limité à des installations facilitant l'activité physique, en particulier dans des régions où le statut socioéconomique est faible et au sein de certains groupes minoritaires 24 , dont les enfants et les adolescents autochtones 25 . Il est évident que la reconnaissance et la prise en compte adéquate de ces inégalités et de l'ensemble des autres inégalités peuvent aider les jeunes adultes à atteindre un indice de masse corporel plus sain, ce que Bhawra et ses collaborateurs 25 , Frankish et ses collaborateurs 26 et…”
unclassified